The Impact of Attitude, Subjective Norm, Perceived Behavioral Control, Trust, Perceived Benefit and Perceived Risk toward KlikBCA Usage Intention in Surabaya - Nikita, Nikita (iBuss Management, 2015)
Bank Central Asia (BCA) and its KlikBCA services have always been a strong market leader in Indonesiaâs internet banking segment. However, as competition between internet banking providers heightens, it is essential for KlikBCA to analyze the factors influencing KlikBCA usage intention. Only then KlikBCA can make informed decision and strategies to retain current users and attract potential users. Hence, the objective of this study is to analyze factors influencing KlikBCA usage intention.The data was gathered using simple random sampling by distributing surveys to 100 KlikBCA users between 20 â 60 years old residing in Surabaya, who have a KlikBCA account and have used it at least once. TheÂ data gathered was analyzed using Multiple Linear Regression Analysis. The result indicates that attitude, subjective norm, perceived behavioral control, perceived benefit, trust and perceived risk simultaneously influence KlikBCA usage intention. When analyzed individually, all factors except subjective norm and trust have significant impact toward KlikBCA usage intention in Surabaya. In addition, perceived behavioral control is the most significant factor affecting usage intention.Keywords: KlikBCA, Theory of Planned Behavior (TPB), Perceived Risk, Perceived Benefit, Trust Â